Elevated triglyceride-glucose index predicts poor outcome in patients with intracranial atherosclerotic stenosis after extracranial and intracranial bypass - Sun, Jun; Zeng, Qiuhua; Wu, Zhimin; Huang, Lixin; Sun, Tao; Ling, Cong; Zhang, Baoyu; Chen, Chuan; Wang, Hui (Annals of medicine (Helsinki), 2024)
The triglyceride-glucose (TyG) index, a novel reliable biomarker for IR that incorporates blood glucose and triglyceride, is linked to intracranial atherosclerotic stenosis (ICAS). In this study, we aimed to further investigate the association between the TyG index and the outcomes of ICAS patients following extracranial-to-intracranial (EC-IC) bypass grafting. 489 ICAS patients who underwent EC-IC bypass between Jan 2009 and Jan 2022 at our hospital were retrospectively collected. The major adverse cardiac and cerebrovascular events (MACCEs), and anastomotic restenosis, both of which are critical factors leading to poor prognosis of ICAS patients after EC-IC bypass, were mainly recorded and analyzed. Kaplan-Meier survival curve and Log-rank tests were sequentially conducted. Cox regression model was used to investigate the association between the TyG index and MACCEs & anastomotic stenosis. C-statistics, continuous net reclassification improvement (NRI), and integrated discrimination improvement (IDI) evaluated the incremental predictive value of the TyG index. A higher incidence of MACCEs and anastomotic stenosis was found in higher-tertile TyG index group. The TyG index was significantly associated with an increased risk of MACCEs and anastomotic stenosis, independent of confounding factors, with a value of HR (1.30, 95%CI 1.10-1.51, < 0.001) and (1.27, 95%CI 1.16-1.40, < 0.001) respectively. The area under the curve (AUC) in the model with the TyG index for predicting the occurrence of MACCEs and anastomotic stenosis were 0.708 (95%CI 0.665-0.748) and 0.731 (95%CI 0.689-0.770) respectively. The addition of the TyG index significantly improved the global performance of the baseline model according to the C-statistics, NRI, and IDI (All < 0.05). Higher TyG levels were associated with poorer outcomes in ICAS patients after EC-IC bypass. TyG could be a key factor in managing ICAS risk and standardizing the indications for EC-IC bypass.